2016
DOI: 10.2337/db16-0714
|View full text |Cite
|
Sign up to set email alerts
|

Circulating CXCR5+PD-1+ICOS+ Follicular T Helper Cells Are Increased Close to the Diagnosis of Type 1 Diabetes in Children With Multiple Autoantibodies

Abstract: Although type 1 diabetes (T1D) is primarily perceived as a T cell-driven autoimmune disease, islet autoantibodies are the best currently available biomarker for autoimmunity and disease risk. These antibodies are produced by autoreactive B cells, the activation of which is largely dependent on the function of CD4CXCR5 follicular T helper cells (Tfh). In this study, we have comprehensively characterized the Tfh- as well as B-cell compartments in a large cohort of children with newly diagnosed T1D or at differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
71
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(84 citation statements)
references
References 38 publications
11
71
0
2
Order By: Relevance
“…So far six major autoantibodies have been identified in T1D: islet cell antibodies (ICA), glutamic acid decarboxylase antibodies (GADA), insulin antibodies (IAA), protein tyrosine phosphatase autoantibodies (IA-2A), zinc transporter 8 antibodies (ZnT8A), and the newly identified tetraspanin 7 antibodies (TSPAN7A). 49 The observation of increased Tfh cells in T1D patients was reproducible in several other studies. Indeed, antigen-experienced memory CD4 + T cells in the blood of T1D patients highly expressed CXCR5, PD-1, ICOS and IL-21, possessing the profile of Tfh.…”
Section: The Aberrant Differentiation and Function Of Tfh Cells In T1dsupporting
confidence: 79%
“…So far six major autoantibodies have been identified in T1D: islet cell antibodies (ICA), glutamic acid decarboxylase antibodies (GADA), insulin antibodies (IAA), protein tyrosine phosphatase autoantibodies (IA-2A), zinc transporter 8 antibodies (ZnT8A), and the newly identified tetraspanin 7 antibodies (TSPAN7A). 49 The observation of increased Tfh cells in T1D patients was reproducible in several other studies. Indeed, antigen-experienced memory CD4 + T cells in the blood of T1D patients highly expressed CXCR5, PD-1, ICOS and IL-21, possessing the profile of Tfh.…”
Section: The Aberrant Differentiation and Function Of Tfh Cells In T1dsupporting
confidence: 79%
“…Interestingly, recent reports documented that diabetic patients have cellular and molecular indicators of increased presence of circulating TFH cells[27,28]. We (unpublished data) and others[29] also found that these indicators are present in the peripheral blood prior to disease onset in AAb-positive (AAb + ) non-diabetic individuals, suggesting that TFH cells might contribute to AAb pathogenesis and T1D development.…”
Section: T1dsupporting
confidence: 68%
“…We were unable to undertake experiments to determine if isolated ICOS + cmT FH cells enhanced production of IgG1 or IgG2 PcP-specific antibodies by isolated memory B cells in cell cultures. However, the functional effect of ICOS + cmT FH cells has been clearly demonstrated for other antigens [34, 35, 69] and our comprehensive analyses of the relationship between PcP-specific IgG antibody responses and memory B cells or cmT FH cells in HIV seronegative subjects and HIV patients provides compelling evidence that production of PcP-specific IgG antibodies requires expansion of ICOS + cmT FH cells. Also, we did not compare study groups for PcP-specific opsonophagocytic antibodies or maintenance of IgG1 and IgG2 antibodies beyond D28 and determine their relationship with ICOS + cmT FH cells, which should be done in future studies.…”
Section: Discussionmentioning
confidence: 75%